Om framstillinga av sørsamar i Trøndelags historie - Leiv Sem (Heimen)
On the depiction of the South Saami people in Trøndelags historie The 2005 publication of a three-volume history of the Trøndelag region ignited a heated debate. Representatives of the indigenous Saami population claimed the editors and authors had omitted the Saamis from the history of the region. This debate was again revived in spring 2017 during the centenary of the first congress of the Saami people in Trondheim 1917. The editor’s reply was that the Saamis indeed had been included, to the degree the historical sources allowed. Using methods of discourse analysis, the article reviews this debate and discusses to which degree, in what way and in which contexts the Saami people are included in the text of Trøndelags historie, and thus integrated in the text’s concept of regional identity. Although differences are to be found between the three volumes and eleven authors, the article argues that the fundamental limitation of the depiction of the Saamis in the text as a whole is not a question of sources. Rather it is a question of the narrative and rhetorical structure of the text, and by extension: of the ideologies of the discourse of the historical community.